A wideband voltage divider for medium voltage measurements - Nongogo, Innocent Sinethemba (Stellenbosch : Stellenbosch University, 2025)
Nongogo, I. S. 2025. A wideband voltage divider for medium voltage measurements. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/0a4b4e4c-4260-4777-9c38-3d46e62eda47